Association of mentally-passive and mentally-active sedentary behaviors with device-measured bouts and breaks of sedentary time in adolescents - André O Werneck; Marcelo Romanzini; Danilo R. Silva; Adewale L. Oyeyemi; Maria R. Bueno; Enio R. V. Ronque (Tabriz University of Medical Sciences, 2021)
Background: Our aim was to analyze the association of self-reported mentally-passive and mentally-active sedentary behaviors with different patterns (bouts and breaks) of device-measured sedentary time in adolescents. Methods: This was a cross-sectional study conducted among 375 adolescents (177 boys) aged 1015 years. Total time, bouts and breaks of sedentary time were measured through accelerometers. Self-reported sedentary behavior in different activities was summed and divided into mentally-active (playing electronic games, studying and reading) and mentally-passive (watching TV, watching DVD, and using computer for leisure). Bayesian linear regression models were used for association analyses. Results: Only mentally-passive sedentary behaviors were positively associated with longer bouts [1-4 minutes: mean posterior distribution: -0.431 (95% credible interval: -0.745 to -0.114); =15 minutes: 0.641 (0.122 to 1.222)] and lower number of breaks [-0.138 (-0.228 to -0.044)] of device-measured sedentary time. Conclusion: Self-reported mentally-passive sedentary behaviors are associated with longer bouts and lower breaks of device-measured sedentary time.